Charakterystyka atrakcyjności inwestycyjnej Europy w świetle bezpośrednich inwestycji zagranicznych - Magdalena Byczkowska; Anna Majzel; Andrzej Kuciński (Ekonomiczne Problemy Usług, 2017)
In reference to the fact that in the subject literature one definition of investment attractiveness does not exist, an attempt has been made to present the essence of the concept - its understanding and classification of the factors that determine this attractiveness. The issue is presented in the context of international capital flows in the form of direct foreign investments. In regard of the fact that not only natural conditions, which cannot be altered by a manor by which he is restrained, determine the investment attractiveness, an attention is drawn to other factors that can be developed by the state and local authorities. It is emphasized that in the time of progressive economic integration and globalization some of the factors are independent from the mentioned entities and are supranational in nature, being subject to unification.